Impacts of topography on spatial variability of temperate understory biomass in closed forest: a case study of Northeast China Tiger and Leopard National Park - WANG Le1,2, MOU Pu2,3, WANG Tianming2,3 (Guangxi Zhiwu)
To investigate the impact of topography on understory biomass, this study employed a nested design and conducted surveys in the Northeast China Tiger and Leopard National Park, involving a total of 138 plots within closed forests, comprising 1 685 plant quadrats. The analysis of topographical effect on understory biomass was carried out using nested analysis of variance and an ordinal logistic regression model. The results were as follows:(1)Among different slope positions, the understory biomass in valleys was higher than on upper slopes, and the footslopes where the understory biomass was the lowest(P<0.01). The understory biomass on shady slopes was lower than on sunny slopes and flats(P<0.01), with no significant difference between the latter two. In terms of different slopes, the understory biomass on steep slopes was higher than on flats, and flats had higher biomass than gentle slopes(P<0.01).(2)There was a significant interaction between slope position and slope aspect. The understory biomass was the highest on flats at the footslopes, flats on upper slopes, upper slopes and sunny slopes, and in valleys among all slope positions. There was no significant difference in understory biomass among shady slopes at the footslopes, sunny slopes at the footslopes, and shady slopes on upper slopes.(3)Ordinal logistic regression analysis of the current state of the study area showed that the probability of high or low understory biomass varied across different combinations of altitude, slope position, and slope aspect. Slope position, slope aspect, and slope had significant effects on the understory biomass. Among the three slope positions, the understory biomass was the highest in valleys and the lowest on footslopes. Among the three slopes, steep slopes had the highest understory biomass, while gentle slopes had the lowest. Shady slopes had the lowest understory biomass compared to other slope aspects.(4)Considering the realistic situation of human disturbance and forest grazing, steep slope areas in valleys had the highest probability of high understory biomass. This study can provide important references for accurately estimating the carrying capacity of understory for preys populations of tiger and leopard in Northeast China Tiger and Leopard National Park, thereby offering a scientific basis for the conservation and management of endangered tigers and leopards.